Indigenous People Participation As A Representation of the Inclusive Development in the New Capital City of Indonesia - Muhamad Arby Hariawan (Jurnal STIA Bengkulu, 2024)
The governments of Indonesia will relocate the capital city in Borneo Island which is called Nusantara Capital City in 2024. This government agenda was designed due to massive ecological and social problems which made Jakarta cannot be a central administration of Indonesia. Nevertheless, multitudinous indigenous people live in the sphere of the proposed region. As a consequence, the authorities of Indonesia should accommodate their participation in order to construct an inclusive capital city which can be lived appropriately. Based on the earlier situation, this research was designed to investigate indigenous people participation as a representation of an inclusive city in Nusantara. Qualitative descriptive method was used to expose comprehensive understanding about local communities' participation to construct an inclusive city in Nusantara. Researcher used Public Participation Theory as the grand analysis. In addition, essential data to strengthen this study was collected by doing several methods such as interview, observation, and literature study. The result of this research explains that the authorities of Indonesia should optimize indigenous people participation. The optimization of local participation can be implemented by constructing a suitable platform which can accommodate their participation electronically. Moreover, massive socialization should be applied as a way to promulgate local communities participation during the governance agendas in the Nusantara Capital City.